AUTENTISITAS DAN SOLIDARITAS: PERSPEKTIF EKSISTENSIALISME TENTANG WOKE CULTURE DALAM PENDIDIKAN KARAKTER SISWA - Devi Indriani; Yundi Fitrah; Ade Kusmana; Bunga Ayu Wulandari; Aditya Reza Haswendra (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to examine the perspective of existentialism, particularly the concepts of authenticity and solidarity, in relation to woke culture within the context of character education. By understanding the relationship between these two schools of thought, this research seeks to explore how existentialism can provide valuable insights in shaping students' character in the modern era. The method used in this study is library research, which involves the analysis of literature related to existentialism, woke culture, and character education. The findings of this research are expected to offer insights for educators and policymakers in formulating more effective educational strategies, as well as helping students find a balance between individual authenticity and social solidarity.